Perceptions and readiness of foodservice establishments at the onset of the COVID-19 Pandemic in Metro Manila and Region IV-A, Philippines - Ebron, Von Ryan M.; Danao, Irma U.; Nguyen-Orca, Marie Faye R.; Orillo, Anna Teresa O.; Parco, Joyce (2022)
The study evaluated the perceptions and readiness of food business operators about COVID-19 through an online survey with respondents from Metro Manila and Region IV-A. Generally, they are knowledgeable about COVID-19 and its transmission, as reflected in their scores. The same is true about their attitude towards “new normal” practices. Years of operation, asset size, and continued operations and delivery services showed significant positive correlation with attitude scores. The resilience of some food business operators may be attributed to having more resources that enabled them to carry the added costs of what the new normal foodservice practices entailed. New normal practices include the implementation of health and safety protocols, shifting business models to online systems, food delivery services, dine-in by reservation, and menu innovations. Food business operators amenable to change and to innovate are more likely to keep afloat during a pandemic.
Keywords: Food service -- Safety measures; COVID-19 pandemic -- Social conditions